المنازعات الإدارية أمام المحكمة الدستورية العليا - الحسين محمد; خشمان مخلد (Latakia University Journal - Economic and Legal Sciences Series, 2017)
هدفت الدراسة إلى التعرف على كيفية اتصال المحكمة الدستورية العليا بالدفع بعدم دستورية قانون أو نظام متعلق بالفصل في الدعوى المنظورة أمام المحكمة الإدارية أو المحكمة الإدارية العليا، حيث كان المشرع الأردني قبل صدور قانون القضاء الإداري رقم 27 لسنة 2014، يعامل محكمة العدل العليا بوصفها احدى الجهات القضائية الخاصة التي لها أن ترفع الدفع بعدم الدستورية مباشرة اسوه بمحكمة التمييز. على خلاف محكمة الموضوع الناظرة للدعوى والتي الزمها بوجوب رفع الدفع بعدم الدستورية إلى محكمة التمييز والتي لها البت في رفع الطعن بعدم الدستورية من عدمه. وفي سبيل ذلك لجأنا إلى المقارنة مع الوضع في مصر وكيفية اتصال الدفع بعدم دستورية قانون أو نظام عند عرض المنازعة الإدارية على محكمة القضاء الإداري أو محكمة الإدارية أو المحكمة الإدارية العليا استنادا لقانون مجلس الدولة رقم 48 لسنة 1979. حيث أناط المشرع المصري بهذه المحاكم أن ترفع الدفع بعدم الدستورية مباشرة إلى المحكمة الدستورية العليا. This paper seeks to compare how the administrative disputes are seen before the Supreme Constitutional Court in relating to allegation of a Non-constitutional law or regulation relates to adjudicate in the case seeing before the Administrative Court or the Supreme Administrative Court in Jordan and Egypt. Therefore, this study aims to highlight how the administrative disputes are seen before the Supreme Constitutional Court in relating to allegation of a Non-constitutional law or regulation relates to adjudicate in the case seeing before the Administrative Court or the Supreme Administrative Court. It is true that prior to the enacting of the Administrative Justice Act No. 27 of 2014 , the Jordanian legislator used to deal with the High Court of Justice as one of the special judicial authorities, which may raise the case of allegation of unconstitutionality directly, similar to the Court of Cassation. Unlike the substantive Court which sees the case, the Jordan legislator obliged it to raise the allegation of unconstitutionality to the Court of Cassation. The Court of Cassation will decide whether to raise the appeal of unconstitutionality or not. As for the Egyptian context, Egypt depends on the law of the State Council No. 48 of 1979. This law 1979 entrusted to Court of Administrative Justice Administrative Court and the Supreme Administrative Court to raise alleged unconstitutionality law directly to the Supreme Constitutional Court.